2013
DOI: 10.3349/ymj.2013.54.5.1104
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Transcatheter Closure of Oval Shaped Atrial Septal Defect with Amplatzer Septal Occluder

Abstract: PurposeFor the successful completion of transcatheter closure of atrial septal defects with the Amplatzer septal occluder, shape of the defects should be considered prior to selecting the device. The purpose of this study is to evaluate the results of a transcatheter closure of oval shaped atrial septal defect.Materials and MethodsFrom November 2009 until November 2011, cardiac computed tomography was performed on 69 patients who needed a transcatheter closure of atrial septal defect. We defined an oval shaped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…An alternative method using a static balloon was developed. 13,20,25 Our results may have been impacted by the pullthrough balloon method used to calibrate the ASD. The formulas we suggest to predict BS may not be accurate with this alternative balloon technique.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…An alternative method using a static balloon was developed. 13,20,25 Our results may have been impacted by the pullthrough balloon method used to calibrate the ASD. The formulas we suggest to predict BS may not be accurate with this alternative balloon technique.…”
Section: Discussionmentioning
confidence: 93%
“…There is no recommended threshold and other authors used a 1.33 value. 20 We demonstrated that the visual analysis is closer to a circular index threshold of 1.4. Our study further allows estimating BS using the 3D maximal ASD diameter with a correction factor according to the shape of the ASD.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…It is not surprising that many ASDs are not circular in shape, and indeed complex ASD shapes have been described by some authors16,19,20,21,22,23). Three-dimensional (3D) images should be reconstructed from 2D images for a complete understanding of defect shape.…”
Section: Shape and Multiplicitymentioning
confidence: 99%